METODE PEMBELAJARAN DENGAN MENGGUNAKAN AUDIT KLINIS BAGI PESERTA DIDIK PROGRAM PENDIDIKAN DOKTER SPESIALIS ONKOLOGI RADIASI DI RSUPNCM/ FKUI - , Fielda Djuita, dr.,Sp.Rad (K) Onk.Rad, Prof. dr. Harsono, Sp.S(K) ([Yogyakarta] : Universitas Gadjah Mada, 2013)
LEARNING METHOD USING CLINICAL AUDIT ON THE MEDICAL SPECIALIST EDUCATION PROGRAMME IN RADIATION ONCOLOGY RESIDENTS AT RSUPNCM/FKUI Introduction: Competency in behaviour domain is one that should be achieved during resident training. One of the efforts is by providing education through personal clinical audit and feedback, which is expected to stimulate self reflection. By doing so, internalization process by the learners can possibly occur which enable them to achieve their competency. Audit with feedback conducted continuously in accordance to Kolbâs learning cycle. Methods : This was a quasi experimental research with time series design. The education done using clinical audit and feedback methods with personal audit instruments that was used by RANZCR which has been modified according to medical records completed by the students. The study was conducted at the Department of Radiotherapy RSUPNCM/FKUI towards 16 radiation oncology students who worked at polyclinic I, II and III at a periode of time between September 2010 until June 2011. Results : The researcher found out the behaviour and compliance of the resident in reporting medical record before and after the education through learning interventions with clinical audit and feedback showed significant differences, where was p = 0,000027 for behaviour. While as the behaviour score after intervention I and after intervention II showed insignificant differences where was p = 0,110. This mean that there were no changes after intervention I and after intervention II. This also indicated that the students have achieved a good xx performance after the first intervention and still at their best performance in the following period. Conclusion : Clinical audit with feedback is one of the learning methods that can improve behavior and compliance of the resident in reporting medical record. This study showed that personal clinical audit can improve behavior of the residents.